A new version of the program fitter for fitting atomic hyperfine structure in optical spectra including the calculation of confidence intervals. (November 2022) - Zeiser, Andreas; Kröger, Sophie; Pooyan-Weis, Ladan; Windholz, Laurentius; Guthöhrlein, Günter
Highlights: Computation of confidence intervals for physical parameters in a non-linear regression of spectroscopic data. Application of statistical methods based on the linearization of the non-linear optimization problem. Extension of a computer program that has been used successfully for many years for determination of physical parameters characterizing the atomic hyperfine structure. Brief overview of the theoretical basics. Demonstration of application with an example. Abstract: The program FITTER, which has been used successfully for many years to analyze the hyperfine structure in atomic and ionic spectra, has been extended. Confidence intervals for all adjusted parameters are now calculated, adding essential information to the results. A brief overview of the theoretical basics of hyperfine structure is given, the calculation of the confidence intervals is presented and the application is discussed using an example.